How effective is public health policy in Scotland on vitamin D deficiency during pregnancy? - Ruth Campbell; Christopher Curran; Jonathan Hayward; Jon Godwin; Susan Johnston; Julie Armstrong; Andrew Collier (Cambridge University Press, 2023)
Abstract Objective: To evaluate the uptake of universal vitamin D supplementation during pregnancy, its effectiveness in preventing vitamin D deficiency and the factors associated with these. Design: The regional public health organisation in Ayrshire, Scotland has a policy of universal provision of vitamin D supplements (10 µg/d) to all pregnant women for the duration of their pregnancy. Pregnant women in this area were recruited at their 12-week antenatal appointment. Blood samples were collected at the 12-week and 34-week appointments. To account for the seasonal variation, women were recruited in two cohorts: summer and winter. Telephone interviews were conducted at 34 weeks to assess the uptake of vitamin D supplements during pregnancy. Other variables were obtained from medical records. Setting: The study was conducted in the NHS Ayrshire and Arran Health Board in Scotland. Participants: 612 pregnant women (aged 15-44 years) living in Ayrshire (latitude 55°), Scotland. Results: Sixty-six percentage took supplementation as recommended. Consumption of supplementation was significantly associated with a higher median serum 25-hydroxyvitamin D concentrations at 34 weeks. Despite this at 34 weeks, 33 % of the summer cohort had insufficient or deficient vitamin D status, while 15 % of the winter cohort had insufficient or deficient status. In multivariable analysis, only adherence and season were independent predictors of vitamin D status. Conclusions: While supplementation improved and maintained vitamin D status during pregnancy, it was not adequate to ensure all those insufficient at 12 weeks achieved sufficient status at the end of pregnancy.